DEVELOPMENT OF ART PERFORMANCE TICKETS INFORMATION SYSTEM AT PUBLIC HIGH SCHOOL - Umniy Salamah; Eka Maulana (Bakti Nusantara Institute, 2020)
The development of technology and increasing human needs are two things that influence each other. As one example is the need to purchase art performance ticket using the internet. At present, most printed tickets allow misuse by irresponsible parties, but it also takes longer to get tickets. Therefore a solution is needed to purchase tickets with the website. In addition to making it easy for buyers and organizers, tickets will be accepted quickly. E-Ticketing is a way to document the sales process of a business activity without having to physically issue valuable documents or paper tickets. A website-based ticket art purchase application is needed to make purchasing process easier. The making of this application uses HTML as client-side development, PHP as server-side development, and MySQL as a database. With this application it is expected to help the organizers and buyers in making it easier to get tickets. In the testing phase this application starts from creating an account to getting a ticket going well. Then from the conclusions of the application made with this application, the buyer will get the convenience of getting tickets and buying tickets for events held at school by opening the website that has been provided.